Publisher Correction: Allele-defined genome of the autopolyploid sugarcane Saccharum spontaneum L. (December 2018) - Zhang, Jisen; Zhang, Xingtan; Tang, Haibao; Zhang, Qing; Hua, Xiuting; Ma, Xiaokai; Zhu, Fan; Jones, Tyler; Zhu, Xinguang; Bowers, John; Wai, Ching; Zheng, Chunfang; et al.
In the version of this article originally published, the accession codes listed in the data availability section were incorrect and the section was incomplete. The text for this section should have read "The genome assembly and gene annotation have been deposited in the NCBI database under accession number QVOL00000000, BioProject number PRJNA483885 and BioSample number SAMN09753102. The data can also be downloaded from the following link:http://www.life.illinois.edu/ming/downloads/Spontaneum_genome/ ." The errors have been corrected in the HTML and PDF versions of the article.